Retraction: He-Wei granules (HWKL) combat cisplatin-induced nephrotoxicity and myelosuppression in rats by inhibiting oxidative stress, inflammatory cytokines and apoptosis. Issue 18 (19th April 2023) - Song, Zehai; Chang, Hang; Han, Na; Liu, Zhihui; Liu, Ye; Wang, Hui; Shao, Jingxuan; Wang, Zhonglin; Gao, Hao; Yin, Jun
Abstract : Retraction of 'He-Wei granules (HWKL) combat cisplatin-induced nephrotoxicity and myelosuppression in rats by inhibiting oxidative stress, inflammatory cytokines and apoptosis' by Zehai Song et al., RSC Adv., 2017, 7, 19794–19807, ; https://doi.org/10.1039/C7RA02830J .